PENYELESAIAN SENGKETA PADA BADAN PERTANAHAN NASIONAL (BPN) ATAS SERTIFIKAT HAK MILIK YANG DIJADIKAN OBYEK HAK TANGGUNGAN - Hudi Karno Sabowo (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2017)
The need for some funds often sought by way of debts with collateral in the form of Certificate of Property Rights. Lenders give receivable amount of money and the debtor receives the money as a debt to be paid to ensure the certificate with the approval of the National Land Agency (BPN) local. Certificate of Property Rights examined by BPN and certainly not in a state of conflict and or controlled by others. With the approval of the Certificate Properties BPN on a piece of land can be used as an object of mortgage. But in practice, it turns out there is a case stating that there has been falsification of certificates Proprietary used as places Encumbrance causing losses for owners of valid Certificate of Property Rights. Forgery that is the starting point disputes that serve Certificate Object Properties Mortgage. The dispute is to be resolved.